COMPARATIVE ANALYSIS OF WORK EFFICIENCY MEASUREMENTS IN THE WIRE HARNESS INDUSTRY - Nurul Ilmi; Sadiq Ardo Wibowo (Journal of Industrial Engineering Management, 2022)
PT XYZ is a company engaged in the wiring harness assembly industry that supplies products to automotive companies in Indonesia. The product of this company is a variant of the part number wiring harness, each of which has a different processing time and employee needs in the assembly process. In the production process for Part No 22-66779-00, PT XYZ divides the work line into three parts, namely the head assembly process (assembly of the product head), the body (assembly of the product body), and the end (assembly of the product tail). The work is conducted based on these parts by many manpower. The problem is that because social distancing is applied, work efficiency in each production line becomes less than optimal. Work productivity decreases and the finished product is past its delivery deadline. In this study, we analyze two scenarios of assembly work on wire harness products. The first scenario is to assemble the head, body, and end separately as PT XYZ has done in the field. While the second scenario is to assemble the heads separately and then carry out the assembly process with the assembly results from the body and end lines (mix body and end). It is resulting in a more efficient assembly process with a lack of time used. The transformation makes improved total time in all the activity processes faster in 2756.38 seconds. The productivity has an increase of 10% than using scenario 1.